Green infrastructure and water quality in the Wadden Sea under future changes in climate - Cobacho, Sara Pino, 1994- (2019)
Verkefnið er lokað til 30.11.2020. Natural shellfish reefs act as Green Infrastructure by protecting the coastline while respecting the natural functioning of the ecosystem. Yet, their efficiency is surrounded by uncertainty as they are subject to Climate Change-related stressors. Identifying their vulnerabilities when exposed to changing water conditions is fundamental to identify the best circumstances for an efficient application of these reefs. An ecological modelling approach enabled the simulation of several future climate scenarios for the Dutch Wadden Sea. Concentrations of dissolved oxygen, nitrate, orthophosphate and Chlorophyll-α were assessed, as well as shellfish biomass as this variable reflected the two-way relationship between the reefs and environmental conditions. The model included Mytilus edulis and Crassostrea gigas, the two dominant reef-forming species in the Dutch Wadden Sea. Orthophosphate concentrations were found to be significantly affected by changes in river outflows increasing up to 25% under RCP8.5, whereas no significant changes in nitrate concentrations were obtained due to high denitrification rates. Irradiance was the main limiting factor for primary production that resulted to be significantly impacted by climate change at most of the monitoring stations. These impacts do not only involve changes in abundance and distribution of phytoplankton but also disturbances to the general pattern of primary productivity. Dissolved oxygen levels were found not to be an issue in the coming years as this variable was not very sensitive to environmental changes. The distribution of shellfish was highly dependent on food availability which caused an eastern migration of these species in search of phytoplankton. In light of these findings, coastal protection strategies that use Green Infrastructure cannot only rely on shellfish reefs as a long-term measure as their continuity in the current locations may vary in the future. This situation would be aggravated in the high emission scenarios, ...